Pendampingan Pengolahan Limbah Kotoran Ayam Petelur Menjadi Pupuk Kompos di Desa Pomahan Kecamatan Pulung Kabupaten Ponorogo - Ahmad Jauhari Anwar; Nanik Setyowati; Nurul Malikah (Social Science Academic, 2025)
This activity aims to increase the knowledge of breeders and farmer regarding the utilization of livestock wasto into compost. An alternative technology that can be applied and has positive prospects is to convert poultry farm waste, namely chicken manure into compost. The target for laying hen farms is to produce compost that can be used by the people of pomahan village, pulung district, ponorogo regency as a short term target, and the long term target is to sell compost to other consumer goods outside the village. Effective technology for community transformation uses method extension, training by making demonstration, or direct practice coupled with mentoring. The method used in this servise research is a qualitative method with an approach to this service, namely ABCD ( asset based community development ) which is oriented to explore and find various problems or potentials owned by the community. The result of this activity is that the community is able to process negative things into positive things, so that from these activities the community is able to manage and become the main actor in gterms of innovation to create useful compost for farmers in the village.